2018
DOI: 10.1172/jci121366
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin regulator Asxl1 loss and Nf1 haploinsufficiency cooperate to accelerate myeloid malignancy

Abstract: ASXL1 is frequently mutated in myeloid malignancies and is known to co-occur with other gene mutations. However, the molecular mechanisms underlying the leukemogenesis associated with ASXL1 and cooperating mutations remain to be elucidated. Here, we report that Asxl1 loss cooperated with haploinsufficiency of Nf1, a negative regulator of the RAS signaling pathway, to accelerate the development of myeloid leukemia in mice. Loss of Asxl1 and Nf1 in hematopoietic stem and progenitor cells resulted in a gain-of-fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…Therefore, it provides a rationale for mechanism-based therapy in patients with genetic or even epigenetic lesions of ASXL1 . Given that mutations of ASXL1 and RAS ( Abdel-Wahab et al, 2012 ) or NF1 ( Zhang et al, 2018b ) often co-occur in myeloid malignancies, it is tempting to generate more relevant models for the understanding of pathophysiological mechanisms and to test potential combination therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it provides a rationale for mechanism-based therapy in patients with genetic or even epigenetic lesions of ASXL1 . Given that mutations of ASXL1 and RAS ( Abdel-Wahab et al, 2012 ) or NF1 ( Zhang et al, 2018b ) often co-occur in myeloid malignancies, it is tempting to generate more relevant models for the understanding of pathophysiological mechanisms and to test potential combination therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two independent groups have reported that the constitutive or conditional deletion of Asxl1 in the hematopoietic system in mice leads to the development of MDS-like defects, including dysplastic neutrophils and cytopenias, which may transform into myeloid leukemia with age ( Abdel-Wahab et al, 2013 ; Wang et al, 2014 ). Using genetic models, Asxl1 loss collaborates with oncogenic NRasG12D mutation ( Abdel-Wahab et al, 2012 ; Wu et al, 2015 ) or haploinsufficiency of Nf1 ( Zhang et al, 2018b ) in bone marrow cells to induce myeloid malignancies. These studies suggest that ASXL1 mutations may function as an early/initiating event in the development of myeloid malignancies, and additional genetic events may cooperate with Asxl1 loss to induce leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the clinical prognosis ( Cui et al, 2015 , 2016 ), hematopoietic-specific deletion of both Asxl1 and Tet2 leads to a much earlier onset of MDS than the deletion of Asxl1 or Tet2 alone. In support, Asxl1 deficiency accompanied with haploinsufficiency of Nf1 or KRas oncogenic mutation accelerates the development of myeloid leukemia in mice ( Abdel-Wahab et al, 2012 ; Zhang et al, 2018 ). Therefore, these models argue that loss of ASXL1 contributes to the initiation and progression of myeloid malignancies, dependent or independent of its H2AK119 deubiquitylation activity.…”
Section: Asxl1 Mutations In Myeloid Malignancies: Loss or Gamentioning
confidence: 97%
“…Our finding that ASXL1 drives BRD4 co-localization with the MAZ transcription could be particularly relevant in this regard. For instance, MAZ has: a known role co-operating with MYC to regulate transcription (Bossone et al, 1992), and disrupted MYC-regulated gene expression was a signature of ASXL1-truncated mice (Yang et al, 2018;Zhang et al, 2018); an SP1-like DNA-binding specificity that is similar to that previously observed for the PR-DUB (Dey et al, 2012); and an ability to interact with the nucleosome-remodelling factor subunit BPTF (Jordan-Sciutto et al, 2000).…”
Section: Discussionmentioning
confidence: 82%